The taxonomic status of the South African straptail, Macruronus capensis Davies, 1950 (Pisces, Gadiformes, Macruronidae) - Leslie, Robin W.; Gon, Ofer; Gouws, Gavin (Zootaxa, 2018)
The first record of the straptail fish, genus Macruronus, from South Africa was based on a single specimen captured off the Atlantic Cape coast and described as a new species, M. capensis Davies 1950. Davies did not examine specimens of the other extant nominal species in the genus, but based his conclusions solely on references to the original descriptions of M. novaezelandiae (Hector 1870) and M. magellanicus Lönnberg 1907. We show that all of the characters used by Davies (1950) to distinguish M. capensis from its congeners are in fact shared by the other nominal species of this genus. We also present molecular evidence from a Macruronus specimen recently caught off South Africa to support the conclusion that M. capensis is a junior synonym of M. novaezelandiae.